2001
DOI: 10.1007/s11627-001-0039-5
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Aerides maculosum lindl. (Orchidaceae)

Abstract: Young leaf segments from plants growing both in vivo and in vitro were cultured on Murashige and Skoog (MS) medium supplemented with auxins [naphthaleneacetic acid (NAA), 2,4-dichlorophenoxyacetic acid (2,4-D)], cytokinins [kinetin (KN) and N 6 -benzyladenine (BA)] and coconut liquid endosperm (CW). The explants from mature leaves did not show any growth and turned necrotic, while those obtained from juvenile leaves growing in vitro developed protocorm-like bodies (PLBs) at their cut surfaces within 4±8 wk dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 7 publications
2
19
0
2
Order By: Relevance
“…Histological analysis showed that at 11-13 days after shoot segment plantation on NP medium, the shape of apical cells in the nodes was changed, then followed by the change of cell shape in the basal part of the nodes, produced bipolar pattern, then gradually developed into shoot (Figure 4f-j). Murthy and Pyati (2001) also reported that the physiological age of an explant is an important factor in plant regeneration. In previous study, Balilashaki et al (2014) reported that buds on the swollen nodes started to grow 2 weeks after emergence, but some other buds remained dormant.…”
Section: Regeneration Of Plantlets From Flower Stalk Nodesmentioning
confidence: 98%
“…Histological analysis showed that at 11-13 days after shoot segment plantation on NP medium, the shape of apical cells in the nodes was changed, then followed by the change of cell shape in the basal part of the nodes, produced bipolar pattern, then gradually developed into shoot (Figure 4f-j). Murthy and Pyati (2001) also reported that the physiological age of an explant is an important factor in plant regeneration. In previous study, Balilashaki et al (2014) reported that buds on the swollen nodes started to grow 2 weeks after emergence, but some other buds remained dormant.…”
Section: Regeneration Of Plantlets From Flower Stalk Nodesmentioning
confidence: 98%
“…Tratamentos ANA BAP A suplementação do meio de cultura com BAP (2 mg.L -1 ) também foi eficiente na formação de protocormóides de Aerides maculosa Lindl. porém a partir de segmentos de folhas jovens de plantas crescidas in vitro (MURTHY, PYATI, 2001). O subcultivo dos protocormóides em meio de cultura MS sem reguladores permitiu a diferenciação dos mesmos em plantas.…”
Section: áPices Radicularesunclassified
“…Essas massas produziram embriões, inicialmente pequenos e brancos, os quais germinaram e passaram por sucessivos estádios de desenvolvimento. Murthy & Pyati (2001) obtiveram protocormos a partir de segmentos de folhas jovens de plantas crescidas in vitro de Aerides maculosa Lindl., em meio de cultura MS suplementado com 2 mg.L -1 de BAP. O subcultivo dos protocormos em meio de cultura MS sem reguladores permitiu a diferenciação dos mesmos em plantas.…”
Section: Resultados E Discussão Efeito Dos Reguladores De Crescimentounclassified